THE USE OF SIMPLE PRESENT TENSE AND ADJECTIVES ON STUDENTS' DESCRIPTIVE WRITING AT PRIVATE VOCATIONAL SCHOOL IN BOGOR - Arif Triyuono; Supeno Supeno (Universitas Indraprasta PGRI, 2021)
The research objective is to analyze the use of Simple Present Tense and Adjectives on students' Descriptive Writing at Private Vocational School in Bogor. The method used in this study is Descriptive text analysis using qualitative data. The procedures are conducted by choosing the text from students' Descriptive writing, analyzing data, interpreting data, and concluding the result of the study. The result shows that 1) there are common errors produced using simple present tense in descriptive writing. The total error is 239 errors which the highest frequency is misformation error which consists of 128 errors or 54%. 2) the total error of using Adjectives in Descriptive writing is 25 errors, and the highest frequency of error is misformation which consists of 17 errors or 68%. The findings in this research are for students' analysis of using Simple Present Tense and Adjectives on Descriptive writing. It occurs because of some reasons they are affected by both Interlingual and Intralingual Error.Keywords: simple present tense; adjectives; descriptive writing